Effect of Sharia Compliance, Islamic Corporate Governance, Islamic Social Reporting on Financial Performance at Islamic Commercial Banks in Indonesia - Tarihoran, Aswin Hidayat; Irfan, Irfan; Astuty, Widia (Budapest International Research and Critics University, 2021)
This study aims to examine and analyze the effect of sharia compliance, Islamic corporate governance, Islamic social reporting on financial performance at Islamic Commercial Banks in Indonesia. This study uses three sub-variables of sharia compliance, namely Islamic income ratio, profit sharing ratio, and zakat performance ratio. The type of research in this study is causal associative. The population of this study are Islamic Commercial Banks registered with the Financial Services Authority in 2015-2019. The sample selection method uses purposive sampling (certain criteria), so the number of samples used is 12 Islamic Commercial Banks so that there are 60 sample data. Data analysis method using structural equation modeling (SEM)-partial least square (PLS) with a significance level of 5%. The results show that the Islamic income ratio has an effect on financial performance, profit sharing ratio has no effect on financial performance and zakat performance ratio has no effect on financial performance. Islamic corporate governance has an effect on financial performance. Islamic social reporting has no effect on financial performance.